Vaping epidemic in US teens: problem and solutions. Issue 2 (30th March 2021) - Venkata, Anand N.; Palagiri, Raga Deepak R; Vaithilingam, Siddharthan
Abstract : Purpose of review: Over the last decade, vaping has emerged into an epidemic of alarming proportions among US teens. This review evaluates the factors leading to the rise of vaping, reasons for its striking popularity among US teens, health consequences of vaping, and measures to mitigate the vaping epidemic. Recent findings: Contemporary research highlights the continued rise of vaping amongst US teens and explains the reasons for its popularity, such as the variety of devices, a wide range of available flavors, youth-targeted advertisements, and lack of awareness of adverse consequences from vaping. This publication highlights current research findings of health consequences of vaping, including a discussion of EVALI (e-cigarette or vaping product use-associated lung injury) and provides an update on strategies to curtail the vaping epidemic. Summary: Vaping has risen to epidemic proportions amongst US teens. This poses a clear and present danger to teens' health with adverse effects ranging from acute lung injury to long-term addiction. This article summarizes key research findings that explain the reasons for the epidemic, health consequences of vaping, and provides an overview of efforts to mitigate the vaping threat to US teens.